Exploring Pharmacy Students’ Perceptions of Feedback and Self-Reflection in Patient Counselling Simulations: Implications for Professional Development - Jessica Pace; Andrew Bartlett; Tiffany Iu; Jessica La; Jonathan Penm (Pharmacy)
(1) Background: Structured use of feedback and self-reflection in simulated counselling sessions has a number of benefits, including identification of strategies for improvement, improvement in key skills and adaptability and a patient-centred approach which will help them to succeed as effective healthcare practitioners. The aim of this study was therefore to explore students’ perceptions of self-reflection and feedback in patient counselling simulations and the development of patient counselling skills; (2) Methods: Focus groups explored student perceptions of how the combination of self-reflection, self-assessment and teacher and peer feedback impacted their performance in simulated patient counselling assessments; (3) Results: Four focus groups with 21 pharmacy students were conducted. We identified three main themes and associated subthemes: consistency and continuity (sub-themes learning through repetitive assessment and inconsistent expectations), perceptions of feedback (sub-themes tutor feedback, peer feedback and self-reflection) and real-life practice (sub-themes authenticity of simulation cases, perceptions of empathy and professional development); (4) Conclusions: This study highlights the critical role of integrating consistent, high-quality feedback, peer assessment, and self-reflection in pharmacy education to enhance students’ learning experiences and prepare them for professional practice. As workplace-based assessment becomes more common and expected by accreditation bodies, these insights underscore the need for structured and continuous feedback processes to be integrated into all areas of pharmacy curricula.